Detailed kinetic study of cumene isopropylation in a liquid-liquid biphasic system using acidic chloroaluminate ionic liquids. - Joni, Joni; Schmitt, Daniel; Schulz, Peter; Lotz, T. J.; Wasserscheid, Peter (Journal of Catalysis, 2008)
A kinetic study of cumene isopropylation has been carried out using the acidic ionic liq. 1-ethyl-3-methylimidazolium chloride ([EMIM]Cl)/AlCl3 (molar ratio 1:2) as the catalyst phase in a semi-batch liq.-liq. biphasic reaction system. Kinetic models representing the alkylation reaction network have been established based on reaction temp. and propylene partial pressure variations. By comparing the results of the kinetic models with the measured concns. in the liq. org. phase, the importance of the different product solubilities in the acidic ionic liq. became evident. Correction of the product concns. in the org. phase based on a COSMO-RS calcn. of the relative product solubilities in the acidic ionic liq. [EMIM][Al2Cl7] gave a remarkably good prediction of the reaction kinetics by the kinetic model. These findings demonstrate the suitability of COSMO-RS to predict the relative solubilities of different arom. compds. in highly reactive catalytic systems. [on SciFinder(R)]
Keywords: cumene isopropylation kinetics biphasic system acidic chloroaluminate ionic liq

Output Impedance Measurement of Digitally Controlled Power Converters in LVDC-Grids - Schwanninger, Raffael; Schmitt, Daniel; Lavery, Melanie; Wunder, Bernd; März, Martin (2024 IEEE Sixth International Conference on DC Microgrids (ICDCM), 2024)
Due to the increase in possible sector couplings to local low voltage DC grids, the amount of controlled infeed converters connected to the grids increases. For these grids to remain stable, proper system analysis is required. While simulation of these systems is possible, the final setup requires measurements. In this paper, the problem of output impedance measurement of digitally controlled power converters, which make up the majority of infeed converters in medium to high power LVDC grids, is discussed. Digital control leads to several requirements regarding the test signals used to measure the converters. Due to the nonlinearity of certain power converter types, the measurements required for a full description of the power converter typically need to be taken for a variety of loads and grid voltages. Wide bandwidth measurements can be used to reduce the overall measurement time. These wide bandwidth measurements require further investigation regarding signal amplitude, which is presented in this pape